Analisis Penerimaan dan Penempatan Karyawan pada UMKM Songket Zainal Kota Palembang (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the employee recruitment and placement process within UMKM Songket Zainal in Palembang. The background of this research lies in the importance of human resource management (HRM) for small and medium enterprises, particularly those in traditional craft industries such as songket weaving. The objective of the study is to describe the recruitment practices, identify weaknesses in employee placement, and evaluate how these processes affect overall work performance. A qualitative descriptive method was employed, with data collected through interviews, observation, and documentation involving the owner and several employees. The findings reveal that recruitment still relies on simple, traditional mechanisms based on recommendations and direct applications without formal assessment of competencies. Employee placement tends to be flexible and based on experience, skills, and worker comfort. However, the absence of standardized selection criteria and structured placement procedures leads to inefficiencies and mismatch of skills. This study implies the need for UMKM to adopt clearer recruitment standards, basic skill tests, and systematic training to enhance employee productivity and organizational effectiveness.